An approach for simulating the interaction between soil and discontinuous structure with mixed interpolation interface. (15th June 2021) - Gong, Jin; Zou, Degao; Kong, Xianjing; Liu, Jingmao; Qu, Yongqian
Highlights: Mixed interpolation interface is introduced to solve discontinuous SSI problems. The introduced method is integrated into FEM frameworks. A crack evolution analysis is carried out for high concrete pedestal. Cracking develops from the upstream of pedestal and extends to inner zone. Abstract: Structural discontinuities are common (e.g. cracks, segmented structures) especially in large-scale geotechnical structures, which can lead to the discontinuous soil-structure interaction (SSI) problems. Thus, in this paper a mixed interpolation interface with non-matching nodes is introduced for effectively simulating discontinuous SSI problems. This paper provides a conveniently executed numerical implementation of the introduced approach within a finite element method (FEM) analysis platform. The high flexibility and precision of the developed method are demonstrated through fine analyses of 2D and 3D concrete faced rockfill dams (CFRDs). Furthermore, a cracking evolution analysis for a high pedestal of the Quxue asphalt concrete core dam is conducted by coupling the method with a cohesive zone model (CZM). The mixed interpolation interface is verified as an effective tool for solving discontinuous SSI problems. The modeling also sheds light on the process of cracking evolution and the primary failure mechanism for high pedestal.